2022
DOI: 10.1002/jvc2.73
|View full text |Cite
|
Sign up to set email alerts
|

Effect of guselkumab on serum biomarkers in Japanese palmoplantar pustulosis patients in a randomized phase 3 study

Abstract: Background It is reported that treatment of palmoplantar pustulosis (PPP) with guselkumab has greater improvement in clinical responses in terms of palmoplantar pustulosis area severity index (PPPASI) score. Here, we present the effect of guselkumab (100 and 200 mg) on PPP‐related serum proteins and their association with clinical responses. Objectives To analyze the effects of guselkumab treatment on PPP‐related circulating serum proteins up to Week 72 and evaluate their association with clinical responses. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Since IL‐17A is usually under the detection level in sera, 9 we measured IL‐22 as a representative of Th17/Th22 cytokines. It was reported that patients with PPP have elevated IL‐17A, IL‐17F, and IL‐22 levels 10 . In fact, in the PPP patients, the mean levels of CitH3, IL‐8, and IL‐22 were higher than those of healthy controls.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Since IL‐17A is usually under the detection level in sera, 9 we measured IL‐22 as a representative of Th17/Th22 cytokines. It was reported that patients with PPP have elevated IL‐17A, IL‐17F, and IL‐22 levels 10 . In fact, in the PPP patients, the mean levels of CitH3, IL‐8, and IL‐22 were higher than those of healthy controls.…”
Section: Discussionmentioning
confidence: 90%
“…In our case, however, the serum calcium levels were normal and a calcipotriol ointment did not exert a sufficient 12 The expression of IL-22 is markedly enhanced in the lesional skin of psoriasis and PPP, and IL-22 levels in the patient's blood are also elevated. 10,13,14 Meanwhile, IL-22 promotes the production of antimicrobial peptides and is involved in the defense against infection. 15 DiGeorge syndrome is easily infectious due to thymic hypoplasia and resultant T cell dysfunction, which may induce the elevation of IL-22 and contribute to the development of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation